Environmental Law and Mining Law in the Framework of State Administration Law - Natasya Arsyiprameswari; Muhamad Adji Rahardian Utama; Seno Adhi Wibowo; Vania Shafira Yuniar (Unnes Law Journal, 2021)
Environment in Indonesia concerning land, water, and air in the territory of the Republic of Indonesia. All these environmental media are the containers where we live, live and breathe. Healthy environmental media will give birth to the current generation of human beings and generations will come a healthy and dynamic. Industrial development, forest exploitation as well as busy and crowded traffic flows due to development that continues to evolve, providing side effects. These side effects result in the land we live in, the water we use for the life and the air we breathe. If the soil, water and air eventually can no longer provide a climate or condition that is feasible for us to use, the pollution or environmental damage has occurred. This study aims to analyze environmental law and mining law provision in the context of state administration law. This study found that some laws and regulations concerning environmental and mining law have been provided, however in fact, there are some overlapping regulations.